Marketing Strategy of L´Oréal Men Expert - Minařík, Martin (2013)
This Master's thesis is focused on the development of a marketing plan and it is divided into two main parts. The first part describes the fundamental theoretical approaches that are suggested to be used during a preparation of any marketing plan. The main topics are segmentation of markets and positioning of brands. The second part is a practical example of an application of this theory on a particular case of the L'Oréal Men Expert brand. In the practical part, the author proposes his own marketing strategy for this brand in the Czech Republic. The information and statistical data about the company and its performance were acquired during an intensive, seven-month-long internship of the author in the marketing department and through an own market research.